A Comparative Study on the Multiscale Mechanical Responses of Human Femoral Neck Between the Young and the Elderly Using Finite Element Method - Cen, Haipeng; Gong, He; Liu, Haibo; Jia, Shaowei; Wu, Xiaodan; Fan, Yubo (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Femoral neck fracture (FNF) is the most serious bone disease in the elderly population. The multiscale mechanical response is a key to predicting the strength of the femoral neck, assessing the risk of FNF, and exploring the role of mechanosensation and mechanotransmission in bone remodeling, especially in the context of aging bone. Methods: Multiscale finite element (FE) models of the proximal femur for both young and elderly people were developed. The models included organ scale (proximal femur), tissue scale (cortical bone), tissue element scale (osteon), and cell scale (osteocyte lacuna-canalicular network (LCN) and extracellular matrix (ECM), OLCEM). The mechanical responses of cortical bone and osteocytes in the mid-femoral neck and the differences in mechanical responses between these two scales were investigated. Results: The mechanical responses of cortical bone and osteocyte showed significant differences between the elderly and the young. The minimum principal strains and mean SEDs of cortical bone in the elderly were 2.067-4.708 times and 3.093-14.385 times of the values in the young, respectively; the minimum principal strains and mean SEDs of osteocyte in the elderly were 1.497-3.246 times and 3.044-12 times of the values in the young, respectively; the amplification factors of minimum principal strain in the inferior (Inf), anterior (Ant), and posterior (Post) quadrants in the young were 1.241-1.804 times of the values in the elderly, but the amplification factor of minimum principal strain in the superior (Sup) quadrant was 87.4% of the value in the elderly; the amplification factors of mean SED in the young were 1.124-9.637 times of the values in the elderly. Conclusions: The mass and bone mineral density (BMD) of cortical bone in the femoral neck is closely related to the mechanical response of osteocytes, which provides a new idea for improving cortical bone quality. Perhaps cortical bone quality could be improved by stimulating osteocytes. Quadrantal differences of bone quality in the mid-femoral neck should be considered to improve fracture risk prediction in the future.